Exterior material for power storage device and power storage device

JP7631390B2Active Publication Date: 2025-02-18LISSENOK PACKAGING CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023018468
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-02-18
Estimated Expiration
2038-05-02

AI Technical Summary

Benefits of technology

【0023】 [1]の発明では、耐熱性樹脂層のさらに外側に設けられた保護樹脂層は、樹脂と、該樹脂に対して相溶性を有しないスペーサー剤と、を含有し、スペーサー剤(凝集物を含む)の一部が、保護樹脂層の表面から外方に突出しているから、本発明の蓄電デバイス用外装材は、耐擦過性に優れている。また、本発明の蓄電デバイス用外装材を成形する際には、スペーサー剤(凝集物を含む)の一部が保護樹脂層の表面から外方に突出していることで、成形型の成形面と保護樹脂層とが直接に接触することが防止されるので、成形性に優れると共に、成形した外装材に変色が生じ難い。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631390000003
    Figure 0007631390000003
  • Figure 0007631390000004
    Figure 0007631390000004
  • Figure 0007631390000005
    Figure 0007631390000005
Patent Text Reader

Abstract

To provide an exterior material for an electricity storage device which has excellent abrasion resistance, excellent formability, and is resistant to discoloration due to forming. [Solution] The protective resin layer 7 includes a heat-resistant resin layer 2 as an outer layer, a heat-sealable resin layer 3 as an inner layer, and a metal foil layer 4 arranged between these two layers. The protective resin layer 7 is laminated further outside the heat-resistant resin layer 2, and contains a resin and a spacer agent that is incompatible with the resin, with part of the spacer agent protruding outward from the surface of the protective resin layer 7.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an exterior material for electricity storage devices such as batteries and capacitors used in portable devices such as smartphones and tablets, and batteries and capacitors used for storing electricity in hybrid automobiles, electric automobiles, wind power generation, solar power generation, and night-time electricity, and to an electricity storage device exteriorly packaged with the exterior material. [Background technology]

[0002] In recent years, as mobile electrical devices such as smartphones and tablet terminals become thinner and lighter, a laminate consisting of a heat-resistant resin layer (base material layer) / outer adhesive layer / metal foil layer / inner adhesive layer / thermally adhesive resin layer (inner sealant layer) is used as the exterior material of the power storage devices such as lithium ion secondary batteries, lithium polymer secondary batteries, lithium ion capacitors, and electric double layer capacitors mounted thereon, instead of the conventional metal can (see Patent Document 1). In addition, power sources for electric vehicles and the like, large power sources for power storage, capacitors, and the like are increasingly being exteriorized with the laminate (exterior material) having the above configuration. The exterior material is molded into a three-dimensional shape such as a substantially rectangular parallelepiped shape by stretch molding or deep drawing. By molding into such a three-dimensional shape, a storage space for accommodating the main body of the power storage device can be secured.

[0003] Also proposed is a configuration in which a matte varnish layer is provided on the outside of the base material layer in order to protect the exterior material and improve formability (see Patent Document 2). Examples of the matte varnish layer include matte varnishes made by adding an appropriate amount of inorganic matting agents such as silica and kaolin to olefin-based or alkyd-based synthetic resins, such as cellulose-based, polyamide-based, vinyl chloride-vinyl acetate-based, modified polyolefin-based, rubber-based, acrylic-based, and urethane-based (see Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-288865 A [Patent Document 2] JP 2011-54563 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the above-mentioned conventional exterior materials are subjected to molding such as bulging to obtain an exterior case, there is a problem in that discoloration occurs on the surface of the exterior case.

[0006] Furthermore, conventional packaging materials have also had the problem that they are prone to defects in appearance, such as scratches, due to rubbing during transportation, etc.

[0007] The present invention has been made in consideration of this technical background, and has an object to provide an exterior material for an electricity storage device that has excellent abrasion resistance, excellent formability, and is less susceptible to discoloration due to molding, and an electricity storage device exteriorized with the exterior material. [Means for solving the problem]

[0008] In order to achieve the above object, the present invention provides the following means.

[0009] [1] An exterior material for an electricity storage device, comprising a heat-resistant resin layer as an outer layer, a heat-fusible resin layer as an inner layer, and a metal foil layer disposed between these layers, A protective resin layer is laminated on the outer side of the heat-resistant resin layer, the protective resin layer contains a resin and a spacer agent that is incompatible with the resin, An exterior material for an electricity storage device, characterized in that a part of the spacer agent protrudes outward from a surface of the protective resin layer.

[0010] [2] The exterior material for an electricity storage device according to item 1, wherein the spacer agent is contained in the protective resin layer in the form of an aggregate of a plurality of spacer agents.

[0011] [3] The exterior material for an electricity storage device according to item 2, wherein the average particle size of each spacer agent constituting the aggregate is 1 μm to 20 μm.

[0012] [4] The exterior material for an electricity storage device according to item 2 or 3, wherein the spacer agent aggregates in the protective resin layer have an average long diameter in a planar view in the range of 10 μm to 120 μm.

[0013] [5] The exterior packaging material for an electricity storage device according to any one of items 2 to 4 above, wherein the spacer agent aggregates protrude outward from the surface of the protective resin layer to a height of 1 μm or more.

[0014] [6] An exterior material for an electricity storage device described in any one of items 2 to 5 above, wherein the planar area of ​​a protruding portion, in which the spacer agent aggregates protrude outward from the surface of the protective resin layer to a protruding height of 1 μm or more, is 4% to 20% of the entire planar area of ​​the protective resin layer.

[0015] [7] An exterior material for an electricity storage device described in any one of items 2 to 4 above, wherein the spacer agent agglomerates protrude outward from the surface of the protective resin layer to a height of 0.5 μm to 10 μm, and the spacer agent agglomerates in the protective resin layer have an average long diameter in a planar view in the range of 10 μm to 120 μm.

[0016] [8] The exterior material for an electricity storage device according to any one of items 1 to 7 above, wherein the spacer agent is one or more types of spacer agents selected from the group consisting of waxes and polymer powders.

[0017] [9] The exterior material for an electricity storage device according to any one of items 1 to 8, wherein the spacer agent has a melting point of 90°C to 350°C.

[0018]

[10] The exterior material for an electricity storage device according to any one of items 1 to 9, wherein a content of the spacer agent in the protective resin layer is 2% by mass to 20% by mass.

[0019]

[11] The packaging material for an electricity storage device according to any one of items 1 to 10, wherein the resin is a reaction product resin of a polyol and a polyisocyanate.

[0020]

[12] An exterior material for a storage battery device described in any one of items 1 to 11 above, wherein the protective resin layer further contains a matting agent consisting of fine particles, and when viewed in a plane of the protective resin layer, the average long diameter of the matting agent in the protective resin layer is in the range of 0.3 μm to 7 μm.

[0021]

[13] An exterior case for an electricity storage device, comprising a molded article of the exterior material for an electricity storage device according to any one of items 1 to 12 above.

[0022]

[14] A main body of an electricity storage device; an exterior member made of the exterior material for an electricity storage device according to any one of items 1 to 12 above and / or the exterior case for an electricity storage device according to item 13 above, The power storage device, wherein the power storage device main body is exteriorly covered with the exterior member. Effect of the Invention

[0023] In the invention of [1], the protective resin layer provided on the outer side of the heat-resistant resin layer contains a resin and a spacer agent that is not compatible with the resin, and a part of the spacer agent (including aggregates) protrudes outward from the surface of the protective resin layer, so that the exterior material for an electric storage device of the present invention has excellent abrasion resistance. In addition, when molding the exterior material for an electric storage device of the present invention, the part of the spacer agent (including aggregates) protrudes outward from the surface of the protective resin layer, which prevents the molding surface of the mold from coming into direct contact with the protective resin layer, so that the exterior material has excellent moldability and is less likely to discolor.

[0024] In the invention [2], the spacer agent is contained in the protective resin layer in the form of an agglomerate of multiple spacer agents. Therefore, when the molding surface of the mold comes into contact with the spacer agent agglomerate (the protruding portion of the agglomerate), the agglomerate easily crumbles and has good slip properties, thereby further improving moldability.

[0025] In the invention [3], the average particle size of each spacer agent constituting the aggregate is 5 μm to 10 μm, so that the aggregate is more likely to crumble when it comes into contact with the molding surface of the mold, thereby further improving the slipperiness.

[0026] In the invention [4], the average major axis of the spacer agent aggregates in the protective resin layer in a plan view is in the range of 30 μm to 120 μm, so that direct contact between the molding surface of the mold and the protective resin layer can be sufficiently prevented.

[0027] In the invention [5], the height to which the spacer agent aggregates protrude outward from the surface of the protective resin layer is 1 μm or more, thereby further improving the abrasion resistance of the exterior material and further preventing discoloration due to molding in the molded exterior material.

[0028] In the invention [6], direct contact between the molding surface of the mold and the protective resin layer can be more sufficiently prevented.

[0029] In the invention [7], direct contact between the molding surface of the mold and the protective resin layer can be more sufficiently prevented.

[0030] In the invention [8], since the above-mentioned specific spacer agent is used, the spacer agent (including spacer agent aggregates) has good dispersibility in the protective resin layer, and outward protrusions can be formed uniformly from the surface of the protective resin layer, thereby stably ensuring excellent abrasion resistance and excellent moldability.

[0031] In the invention [9], the melting point of the spacer agent is 90°C to 180°C, so that the protective resin layer can be formed without the spacer agent melting during drying when the protective resin layer is formed, and the shape of the spacer agent can be maintained when the battery element is heat-sealed with an exterior material.

[0032] In the invention

[10] , the content of the spacer agent in the protective resin layer is 2% by mass to 20% by mass. When the content is 2% by mass or more, excellent abrasion resistance and excellent formability can be sufficiently ensured, and when the content is 20% by mass or less, the protective function of the protective resin layer can be sufficiently exhibited.

[0033] In the invention

[11] , the chemical resistance (solvent resistance, acid resistance, etc.) of the exterior material can be further improved.

[0034] In the invention

[12] , the protective resin layer further contains a matting agent consisting of fine particles, and when viewed in a planar view of the protective resin layer, the average long diameter of the matting agent in the protective resin layer is in the range of 0.3 μm to 7 μm. Therefore, the matte appearance can be easily adjusted, and the desired appearance can be reliably expressed.

[0035] According to the invention

[13] , it is possible to provide an exterior case for an electricity storage device that is excellent in abrasion resistance and is well-formed and does not discolor.

[0036] The invention of

[14] provides an electricity storage device that is exteriorly packaged with an exterior member having excellent abrasion resistance. [Brief description of the drawings]

[0037] [Figure 1] 1 is a cross-sectional view showing one embodiment of an exterior material for an electricity storage device according to the present invention. [Diagram 2] FIG. 2 is an enlarged schematic cross-sectional view of a portion of the outer layer and the protective layer. [Diagram 3] 1 is a cross-sectional view showing one embodiment of an electricity storage device according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] One embodiment of the exterior material 1 for a power storage device according to the present invention is shown in FIG. 1. In this exterior material 1 for a power storage device, a heat-resistant resin layer (outer layer) 2 is laminated and integrated on one surface (upper surface) of a metal foil layer 4 via a first adhesive layer 5, and a heat-sealable resin layer (inner layer) 3 is laminated and integrated on the other surface (lower surface) of the metal foil layer 4 via a second adhesive layer 6, and a protective resin layer 7 is laminated on the outside of the heat-resistant resin layer 2 (on the side opposite to the metal foil layer 4 side in the heat-resistant resin layer 2). In this embodiment, the protective resin layer 7 is laminated directly on the outer surface of the heat-resistant resin layer 2 (on the side opposite to the metal foil layer 4 side in the heat-resistant resin layer 2) (see FIG. 1). In this embodiment, a resin composition is applied directly to the outer surface of the heat-resistant resin layer 2 by a gravure coating method, and the protective resin layer 7 is laminated.

[0039] The heat-resistant resin layer (outer layer) 2 is a member that mainly plays a role in ensuring good formability of the packaging material 1, that is, it plays a role in preventing breakage due to necking of the metal foil during forming.

[0040] The heat-resistant resin used for constituting the heat-resistant resin layer (outer layer) 2 is a heat-resistant resin that does not melt at the heat-sealing temperature when heat-sealing the electrical storage device exterior material 1. As the heat-resistant resin, a heat-resistant resin having a melting point 10° C. or more higher than the melting point of the resin constituting the heat-fusible resin layer 3 is preferably used, and a heat-resistant resin having a melting point 20° C. or more higher than the melting point of the resin constituting the heat-fusible resin layer 3 is particularly preferably used.

[0041] The heat-resistant resin layer (outer layer) 2 is not particularly limited, and examples thereof include stretched polyamide films such as stretched nylon films, stretched polyester films, etc. Among them, it is particularly preferable to use biaxially stretched polyamide films such as biaxially stretched nylon films, biaxially stretched polybutylene terephthalate (PBT) films, biaxially stretched polyethylene terephthalate (PET) films, or biaxially stretched polyethylene naphthalate (PEN) films as the heat-resistant resin stretched film layer 2. It is also preferable to use a heat-resistant resin biaxially stretched film stretched by a simultaneous biaxial stretching method as the heat-resistant resin stretched film layer 2. The nylon is not particularly limited, and examples thereof include nylon 6, nylon 6,6, and MXD nylon. The heat-resistant resin layer 2 may be formed of a single layer (single stretched film), or may be formed of a multilayer structure consisting of, for example, a stretched polyester film / stretched polyamide film (multilayer structure consisting of a stretched PET film / stretched nylon film, etc.).

[0042] The heat-resistant resin layer (outer layer) 2 may be a resin layer formed by applying a heat-resistant resin.

[0043] The thickness of the heat-resistant resin layer 2 is preferably 12 μm to 50 μm. When a polyester resin is used, the thickness is preferably 12 μm to 50 μm, and when a nylon resin is used, the thickness is preferably 15 μm to 50 μm. By setting the thickness to be equal to or greater than the above-mentioned preferable lower limit, sufficient strength for the exterior packaging material 1 can be ensured, and by setting the thickness to be equal to or less than the above-mentioned preferable upper limit, stress during stretch forming or draw forming can be reduced, improving formability.

[0044] In the present invention, a protective resin layer 7 must be laminated on the outer side of the heat-resistant resin layer 2 (on the side of the heat-resistant resin layer 2 opposite to the metal foil layer 4). The protective resin layer 7 contains a resin and a spacer agent 8 that is incompatible with the resin, and a part of the spacer agent 8 protrudes outward from the surface of the protective resin layer 7 (see FIG. 2).

[0045] In this embodiment, the spacer agent is dispersed and contained in the protective resin layer 7 in the form of a plurality of spacer agent aggregates 8 (see FIG. 2). The average particle size of each spacer agent constituting the aggregates is preferably 1 μm to 20 μm, and particularly preferably 5 μm to 10 μm. The major axis of the spacer agent aggregates 8 in the protective resin layer 7 is preferably in the range of 10 μm to 120 μm. In particular, the major axis of the spacer agent aggregates 8 in the protective resin layer 7 is more preferably in the range of 40 μm to 70 μm, and particularly preferably in the range of 50 μm to 60 μm.

[0046] The spacer agent 8 or spacer agent aggregates 8 preferably have a protruding height H of 1 μm or more protruding outward from the surface of the protective resin layer 7 (see FIG. 2). By having a protruding height H of 1 μm or more, the scratch resistance of the exterior packaging material 1 can be further improved, and when the exterior packaging material 1 is molded, the molding surface of the mold and the protective resin layer 7 are prevented from coming into direct contact with each other, resulting in excellent moldability and less discoloration of the molded exterior packaging material. Of these, it is more preferable that the protruding height H is in the range of 1.5 μm to 10.0 μm.

[0047] Furthermore, the planar area of ​​the protruding portion where the spacer agent 8 and / or the spacer agent aggregates 8 protrude outward from the surface of the protective resin layer 7 to a protruding height of 1 μm or more is preferably 4% to 20% of the entire planar area of ​​the protective resin layer 7, more preferably 6% to 15%, and particularly preferably 5% to 10%.

[0048] The resin constituting the protective resin layer 7 is not particularly limited, but it is preferable to use a reaction product resin between a polyol and a polyisocyanate. The polyol is not particularly limited, but examples thereof include polyester polyol, polyurethane polyol, polyether polyol, etc. The weight average molecular weight (Mw) of the polyol is preferably 3,000 to 50,000.

[0049] The polyisocyanate is not particularly limited, and examples thereof include tolylene diisocyanate (TDI), hexamethylene diisocyanate (HMDI), a trimethylolpropane adduct of TDI, a trimethylolpropane adduct of HMDI, etc. Among them, it is preferable to use a trimethylolpropane adduct of TDI, a trimethylolpropane adduct of HMDI, or a "mixture of a trimethylolpropane adduct of TDI and a trimethylolpropane adduct of HMDI" as the polyisocyanate.

[0050] The spacer agent 8 is not particularly limited, but it is preferable to use one or more spacer agents selected from the group consisting of waxes and polymer powders. The waxes are not particularly limited, but examples thereof include paraffin wax, microcrystalline wax, hydrocarbon wax, low molecular weight polyethylene wax, etc. The polymer powder is not particularly limited, but examples thereof include ultra-high molecular weight polyethylene powder, polyethylene powder, low molecular weight polyethylene powder, polypropylene powder, low molecular weight polypropylene powder, etc.

[0051] The weight average molecular weight (simply "molecular weight" when there is no molecular weight distribution) of the spacer agent 8 is preferably 100 to 6,000,000, more preferably in the range of 1,000 to 8,000, and particularly preferably in the range of 1,000 to 6,000.

[0052] The melting point of the spacer agent 8 is preferably from 50°C to 350°C, more preferably from 50°C to 180°C, and particularly preferably from 90°C to 160°C.

[0053] The density of the spacer agent 8 is 0.85 g / cm 3 ~3.0g / cm 3 and preferably 0.88 g / cm 3 ~2.3g / cm 3 It is more preferable that:

[0054] The content of the spacer agent in the protective resin layer 7 is preferably 2% by mass to 20% by mass. When the content is 2% by mass or more, excellent abrasion resistance and excellent formability can be sufficiently ensured, and when the content is 20% by mass or less, the protective function of the protective resin layer can be sufficiently exhibited. In particular, the content of the spacer agent in the protective resin layer 7 is preferably 5% by mass to 15% by mass. Also, the content of the resin in the protective resin layer 7 is preferably 60% by mass to 98% by mass.

[0055] The protective resin layer 7 may further contain a matting agent made of fine particles. In this case, it is preferable that the average value of the major axis of the matting agent in the protective resin layer 7 is in the range of 0.3 μm to 7 μm in the plan view of the protective resin layer 7. The matting agent is a fine particle that forms an uneven shape on the surface of the protective resin layer 7 and diffuses light, thereby reducing the glossiness of the surface of the protective resin layer 7 and forming an appearance with a calm texture. The matting agent is not particularly limited, and examples thereof include inorganic fine particles (e.g., barium sulfate fine particles, silica fine particles, etc.), and resin beads (e.g., acrylic resin beads, styrene resin beads, etc.). It is particularly preferable that the average particle diameter of the matting agent is in the range of 0.5 μm to 5 μm. When barium sulfate fine particles are used as the matting agent, it is preferable to use barium sulfate fine particles having an average particle diameter of 0.3 μm to 3 μm. Furthermore, when acrylic resin beads are used as the matting agent, it is preferable to use acrylic resin beads having an average particle diameter of 3 μm to 5 μm.

[0056] The thickness of the protective resin layer 7 (thickness after drying; excluding the protruding portions of the spacer agent) is preferably 0.5 μm to 10 μm.

[0057] The method for forming the protective resin layer 7 is not particularly limited, but for example, an aqueous emulsion (water-based emulsion) containing the above-mentioned resin and the spacer agent 8 can be applied to the surface of the heat-resistant resin layer 2 and dried to form the protective resin layer 7. The application method is not particularly limited, but examples thereof include a spray coating method, a gravure roll coating method, a reverse roll coating method, and a lip coating method.

[0058] The heat-sealable resin layer (inner layer) 3 has the function of imparting excellent chemical resistance to highly corrosive electrolytes used in lithium ion secondary batteries and the like, and also of imparting heat sealability to the exterior material.

[0059] The heat-sealable resin layer 3 is preferably, but not limited to, a thermoplastic resin unstretched film layer. The thermoplastic resin unstretched film layer 3 is preferably, but not limited to, an unstretched film made of at least one thermoplastic resin selected from the group consisting of polyethylene, polypropylene, olefin copolymers, acid-modified products thereof, and ionomers.

[0060] The thickness of the heat-sealable resin layer 3 is preferably set to 20 μm to 80 μm. By setting the thickness to 20 μm or more, the occurrence of pinholes can be sufficiently prevented, and by setting the thickness to 80 μm or less, the amount of resin used can be reduced, thereby enabling cost reduction. In particular, the thickness of the heat-sealable resin layer 3 is particularly preferably set to 30 μm to 50 μm. The heat-sealable resin layer 3 may be a single layer or multiple layers.

[0061] A lubricant is usually added to the heat-sealable resin layer 3. The addition of the lubricant can improve moldability during molding. The content of the lubricant in the heat-sealable resin layer 3 is preferably set in the range of 200 ppm to 5000 ppm.

[0062] The lubricant is not particularly limited, but examples thereof include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides.

[0063] The metal foil layer 4 plays a role of imparting gas barrier properties that prevent the intrusion of oxygen and moisture to the packaging material 1. The metal foil layer 4 is not particularly limited, but examples thereof include aluminum foil and copper foil, and aluminum foil is generally used. The thickness of the metal foil layer 4 is preferably 20 μm to 100 μm. By having a thickness of 20 μm or more, it is possible to prevent the occurrence of pinholes during rolling in manufacturing the metal foil, and by having a thickness of 100 μm or less, it is possible to reduce stress during stretch forming or drawing, thereby improving formability.

[0064] It is preferable that at least the inner surface 4a (the surface on the second adhesive layer 6 side) of the metal foil layer 4 is subjected to a chemical conversion treatment. By performing such a chemical conversion treatment, corrosion of the metal foil surface due to the contents (battery electrolyte, food, medicine, etc.) can be sufficiently prevented. For example, the chemical conversion treatment is performed on the metal foil by carrying out the following treatment. That is, for example, the surface of the metal foil that has been subjected to a degreasing treatment is subjected to the following treatment. 1) An aqueous solution consisting of a mixture of metal salts of phosphoric acid, chromate and fluoride 2) An aqueous solution consisting of a mixture of phosphoric acid, chromic acid, and fluoride metal salts and nonmetal salts. 3) A chemical conversion treatment is carried out by applying an aqueous solution of a mixture of an acrylic resin and / or a phenolic resin, phosphoric acid, chromic acid, and a metal fluoride salt, followed by drying.

[0065] The first adhesive layer (outer adhesive layer) 5 is not particularly limited, and examples thereof include an adhesive layer formed of a two-liquid reactive adhesive. Examples of the two-liquid reactive adhesive include a two-liquid reactive adhesive composed of a first liquid consisting of one or more polyols selected from the group consisting of polyurethane polyols, polyester polyols, and polyether polyols, and a second liquid (curing agent) consisting of polyisocyanate. The first adhesive layer 5 is, for example, a two-liquid reactive adhesive or other adhesive applied to the "upper surface of the metal foil layer 4" and / or the "lower surface of the heat-resistant resin layer 2" by gravure printing. The layer is formed by applying the layer by a coating method or the like.

[0066] The second adhesive layer (inner adhesive layer) 6 is not particularly limited, and examples thereof include adhesive layers formed from polyurethane adhesives, acrylic adhesives, epoxy adhesives, polyolefin adhesives, elastomer adhesives, fluorine adhesives, etc. Among these, it is preferable to use a two-liquid reactive adhesive composed of a first liquid made of an acid-modified olefin resin (maleic anhydride-modified polypropylene, maleic anhydride-modified polyethylene, etc.) and a second liquid (curing agent) made of polyisocyanate, and in this case, the electrolyte resistance and water vapor barrier properties of the exterior material 1 can be further improved.

[0067] In the above embodiment, a configuration is adopted in which the first adhesive layer 5 and the second adhesive layer 6 are provided, but neither of these layers 5, 6 are essential constituent layers, and a configuration in which they are not provided can also be adopted.

[0068] Thus, by forming (deep drawing, stretch forming, etc.) the exterior material 1 for an electricity storage device according to the present invention, an exterior case 1A for an electricity storage device as shown in Fig. 3 can be obtained. The shape of the exterior case 1A for an electricity storage device is not particularly limited, but examples thereof include a substantially rectangular parallelepiped shape with one surface (top surface) open as shown in Fig. 3.

[0069] Next, one embodiment of an electricity storage device 30 according to the present invention is shown in Fig. 3. As shown in Fig. 3, an electricity storage device main body 31 having a substantially rectangular parallelepiped shape is accommodated in an accommodating recess of an exterior case 1A obtained by molding an exterior material for an electricity storage device 1 of the present invention, and the exterior material for an electricity storage device 1 of the present invention is placed on top of the electricity storage device main body 31 with its inner layer 3 side facing inward (lower side), and the peripheral portion of the inner layer 3 of the planar exterior material 1 and the inner layer 3 of a flange portion (sealing peripheral portion) 29 of the exterior case 1A are heat-sealed and sealed to form the electricity storage device 30 of the present invention.

[0070] In FIG. 4, reference numeral 39 denotes a heat-sealed portion where the peripheral portion of the exterior material 1 and the flange portion (sealing peripheral portion) 29 of the exterior case 1A are joined (welded).

[0071] The electricity storage device main body 31 is not particularly limited, but examples thereof include a battery main body, a capacitor main body, and a condenser main body. EXAMPLES

[0072] Next, specific examples of the present invention will be described, but the present invention is not particularly limited to these examples.

[0073] <Spacer agent used> (Polyethylene wax A) Average particle size: 9μm, weight average molecular weight (Mw): 3000, melting point: 120℃, density: 0.96g / cm 3 Polyethylene wax (waxes) (Polyethylene wax B) Average particle size: 12 μm, weight average molecular weight (Mw): 4000, melting point: 128°C, density: 0.98 g / cm 3 Polyethylene wax (waxes) (Polyethylene wax C) Average particle size: 5μm, weight average molecular weight (Mw): 6000, melting point: 116℃, density: 0.95g / cm 3 Polyethylene wax (waxes) (PTFE wax D) Average particle size: 2μm, weight average molecular weight (Mw): 5000, melting point: 320℃, density: 2.10g / cm 3 Polytetrafluoroethylene (PTFE) wax (waxes) ) (Low molecular weight polyethylene powder) Average particle size: 20 μm, weight average molecular weight (Mw): 8500, melting point: 121°C, density: 0.94 g / cm 3 Low molecular weight polyethylene (PE) powder (Low molecular weight polypropylene powder) Average particle size: 15 μm, weight average molecular weight (Mw): 7000, melting point: 145°C, density: 0.89 g / cm 3 Low molecular weight polypropylene (PP) powder.

[0074] <Example 1> Resin composition A for forming a protective resin layer was obtained by mixing 100 parts by mass of polyester polyol having a weight average molecular weight (Mw) of 9,800, 15 parts by mass of a trimethylolpropane adduct of hexamethylene diisocyanate (TMP adduct of HMDI) as a polyisocyanate, 5 parts by mass of the above-mentioned polyethylene wax A (waxes) as a spacer agent, 12 parts by mass of acrylic resin beads having an average particle diameter of 2 μm as a first matting agent, 3 parts by mass of barium sulfate having an average particle diameter of 0.8 μm as a second matting agent, and 200 parts by mass of a mixed solvent of toluene and methyl ethyl ketone (100 parts by mass of toluene + 100 parts by mass of methyl ethyl ketone).

[0075] In this resin composition A for forming a protective resin layer, the ratio of NCO of the polyisocyanate to OH of the polyester polyol (NCO / OH) was 1.8.

[0076] Next, the above-mentioned resin composition A for forming a protective resin layer was applied by a gravure roll coating method to one side of a biaxially oriented nylon (6 nylon) film 2 having a thickness of 15 μm obtained by stretching using the simultaneous biaxial stretching method, and then dried. The resin composition A was then left in an environment of 60° C. for 3 days to allow the curing reaction to proceed, resulting in a formation amount of 2.5 g / m 2 A protective resin layer 7 was formed.

[0077] On the other hand, a chemical conversion treatment solution consisting of polyacrylic acid, metal chromate, phosphoric acid, water, and isopropyl alcohol (IPA) was applied to both sides of an aluminum foil 4 (O material specified in JIS A8021) having a thickness of 35 μm, and the resulting coating was dried at 180° C. to a chromium deposition amount of 10 mg / m 2 It was made so that:

[0078] Next, the other side of the biaxially oriented nylon film 2 (the side opposite to the side on which the protective resin layer 7 is formed) was bonded to one side of the chemically treated aluminum foil 4 via a two-component curing polyester-based polyurethane outer adhesive 5 containing polyester polyol and a trimethylolpropane adduct of tolylene diisocyanate (TMP adduct of TDI), and then a 30 μm-thick unstretched polypropylene film (heat-fusible resin layer) 3 was bonded to the other side 4a of the aluminum foil 4 via a two-component curing inner adhesive 6 containing maleic anhydride-modified polypropylene and hexamethylene diisocyanate (HMDI), and the resulting mixture was left in a 40° C. environment for 5 days to obtain an exterior material for a storage battery device 1 as shown in FIG. 1.

[0079] The unstretched polypropylene film 3 used was a three-layered film consisting of a 4 μm random polypropylene layer (erucic acid amide content 1000 ppm, silica fine particle content 5000 ppm) / 22 μm block polypropylene layer (erucic acid amide content 2000 ppm) / 4 μm random polypropylene layer (erucic acid amide content 1000 ppm, silica fine particle content 5000 ppm). The coating amount of the outer adhesive 5 was 3 g / m2. 2 and the coating amount of the inner adhesive 6 was set to 3 g / m 2 was set to.

[0080] <Example 2> An exterior material 1 for a power storage device shown in FIG. 1 was obtained in the same manner as in Example 1, except that the blending amount of polyethylene wax A (waxes) in the resin composition for forming a protective resin layer was changed to 10 parts by mass.

[0081] <Example 3> An exterior material 1 for a power storage device shown in FIG. 1 was obtained in the same manner as in Example 1, except that the blending amount of polyethylene wax A (waxes) in the resin composition for forming a protective resin layer was changed to 15 parts by mass.

[0082] <Example 4> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 2, except that, as the polyisocyanate, "8 parts by mass of a trimethylolpropane adduct of hexamethylene diisocyanate (TMP adduct of HMDI) and 7 parts by mass of a trimethylolpropane adduct of tolylene diisocyanate (TMP adduct of TDI)" was used instead of 15 parts by mass of a trimethylolpropane adduct of hexamethylene diisocyanate (TMP adduct of HMDI).

[0083] <Example 5> An outer casing material 1 for a power storage device shown in FIG. 1 was obtained in the same manner as in Example 4, except that 100 parts by mass of a polyurethane polyol having a weight average molecular weight (Mw) of 14,500 was used instead of 100 parts by mass of a polyester polyol having an Mw of 9,800, and 10 parts by mass of the polyethylene wax B (waxes) was used instead of 10 parts by mass of "polyethylene wax A".

[0084] <Example 6> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 4, except that 5 parts by mass of the PTFE wax D (waxes) was used instead of 10 parts by mass of "polyethylene wax A".

[0085] <Example 7> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 5, except that 5 parts by mass of the PTFE wax D (waxes) was used instead of 10 parts by mass of "polyethylene wax B".

[0086] <Example 8> An exterior material 1 for a power storage device shown in FIG. 1 was obtained in the same manner as in Example 7, except that, as the first matting agent, 12 parts by mass of urethane resin beads having an average particle diameter of 3 μm were used instead of 12 parts by mass of acrylic resin beads having an average particle diameter of 2 μm.

[0087] <Example 9> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 8, except that 5 parts by mass of the above-mentioned "polyethylene wax C" was used instead of 5 parts by mass of "PTFE wax D".

[0088] <Example 10> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 7, except that 3 parts by mass of the low-molecular-weight PE powder was used instead of 5 parts by mass of "PTFE wax D".

[0089] <Example 11> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 7, except that 5 parts by mass of the low-molecular-weight PE powder was used instead of 5 parts by mass of "PTFE wax D".

[0090] <Example 12> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 7, except that 3 parts by mass of the low-molecular-weight PP powder was used instead of 5 parts by mass of "PTFE wax D".

[0091] <Example 13> An exterior material for a power storage device 1 shown in FIG. 1 was obtained in the same manner as in Example 7, except that 5 parts by mass of the low-molecular-weight PP powder was used instead of 5 parts by mass of "PTFE wax D".

[0092] <Example 14> An outer casing material 1 for a power storage device shown in FIG. 1 was obtained in the same manner as in Example 1, except that 100 parts by mass of a polyurethane polyol having a weight average molecular weight (Mw) of 14,500 was used instead of 100 parts by mass of a polyester polyol having an Mw of 9,800, and 3 parts by mass of the low molecular weight PE powder was used instead of 5 parts by mass of "polyethylene wax A".

[0093] <Example 15> An exterior material 1 for a power storage device as shown in FIG. 1 was obtained in the same manner as in Example 1, except that 100 parts by mass of a polyurethane polyol having a weight average molecular weight (Mw) of 14,500 was used instead of 100 parts by mass of a polyester polyol having an Mw of 9,800, and 3 parts by mass of the low molecular weight PP powder was used instead of 5 parts by mass of "polyethylene wax A".

[0094] <Comparative Example 1> An exterior material for an electricity storage device was obtained in the same manner as in Example 1, except that the resin composition for forming a protective resin layer was not blended with (contained) polyethylene wax A (spacer agent).

[0095] [Table 1]

[0096] [Table 2]

[0097] In Tables 1 and 2, the details (type, average particle size, amount blended) of the first matting agent and the second matting agent are omitted (these are described in the above Examples section).

[0098] Each of the exterior materials for electricity storage devices obtained as described above was evaluated according to the following evaluation methods. The results are shown in Tables 1 and 2.

[0099] In addition, the "protrusion height H (μm)" in Table 1 is the average value (protrusion height H) obtained by averaging the protrusion heights of 10 spacer agent agglomerates protruding outward from the surface of the protective resin layer by observing the cross section of the exterior material for an electricity storage device (see Figure 2) with an SEM (scanning electron microscope), and measuring these 10 protrusion heights.

[0100] In addition, the "area ratio (%) of protruding parts in a plan view with a protruding height of 1 μm or more" in Table 1 is calculated by measuring the surface of the protective resin layer side of the exterior material for an electricity storage device by a SEM (scanning electron microscope) in a square area of ​​50 μm length × 50 μm width (2500 μm 2 That is, the "planar area of ​​the protruding portion where the spacer agent aggregate protrudes outward from the surface of the protective resin layer to a height of 1 μm or more" obtained by the planar observation using the SEM is defined as "S(μm 2 )" is the area ratio calculated using the following formula.

[0101] Area ratio (%) = (S / 2500) x 100 In addition, the "longest diameter of the aggregates" in Table 1 is the average value (average long diameter of the spacer agent aggregates) obtained by observing in plan the surface of the protective resin layer side of the exterior material for electricity storage devices using a SEM (scanning electron microscope), determining the long diameters (W) in plan view of 10 randomly selected spacer agent aggregates using this planar observation with the SEM (see Figure 2).

[0102] <Abrasion resistance evaluation method> Using a Gakushin method friction fastness tester (with an aluminum jig with a load of 200 g) manufactured by Tester Sangyo Co., Ltd., the aluminum jig was brought back and forth in contact with the surface of the exterior material for a storage battery device (surface of protective resin layer 7) 10 times, and the presence or absence and the extent of scratches on the surface were then visually inspected, and the abrasion resistance was evaluated based on the following judgment criteria. (Judgment criteria) "○": No scratches on the surface of the protective resin layer "△": Slight scratches are observed on the surface of the protective resin layer, but are barely noticeable. "X": Scratches were clearly observed on the surface of the protective resin layer.

[0103] <Evaluation method for discoloration prevention> A first exterior case for a power storage device (rectangular solid-shaped molded body with an open top) 1A having a rectangular parallelepiped shape of 55 mm long x 35 mm wide x 4 mm deep is obtained by applying a pressure of 0.3 MPa to the exterior material for the power storage device using an embossing machine (product number: TP-25C-X2) manufactured by Amada Co., Ltd. The presence or absence and the degree of discoloration on both sides of the first exterior case obtained were visually examined, and the discoloration prevention property was evaluated based on the following criteria. The evaluation results are shown in Table 2.

[0104] The exterior material for the power storage device was subjected to bulging molding in the same manner as above with a pressure of 0.25 MPa to obtain a second exterior case for the power storage device (a rectangular solid-shaped molded body with an open top) 1A having a rectangular parallelepiped shape of 55 mm long x 35 mm wide x 6 mm deep (see FIG. 3). Both sides of the obtained second exterior case were visually inspected for the presence or absence of discoloration and the degree of discoloration, and the discoloration prevention property was evaluated based on the following criteria. The evaluation results are shown in Table 2.

[0105] (Judgment criteria) "◎": No discoloration was observed on either side of the exterior case before or after molding. "○": Very slight discoloration was observed on the surface of the protective resin layer of the exterior case before and after molding, but this was not a problem for the product. "△": Slight discoloration was observed on the surface of the protective resin layer of the exterior case before and after molding, but it was still usable as a product. "X": Clear discoloration was observed on the surface of the protective resin layer side of the exterior case before and after molding.

[0106] As is clear from the table, the exterior packaging materials for electricity storage devices of Examples 1 to 15 according to the present invention were excellent in abrasion resistance, and also had excellent discoloration prevention properties, being less susceptible to discoloration due to molding.

[0107] In contrast, in Comparative Example 1 in which no spacer agent was added to the protective resin layer, the scratch resistance was insufficient and the resistance to discoloration due to molding was poor. [Industrial Applicability]

[0108] Specific examples of the exterior material for an electricity storage device according to the present invention include, for example, - Energy storage devices such as lithium secondary batteries (lithium ion batteries, lithium polymer batteries, etc.) Lithium-ion capacitor Electric double layer capacitor The electric storage device according to the present invention is used as an exterior material for various electric storage devices such as those exemplified above. In addition, the electric storage device according to the present invention also includes an all-solid-state battery. [Explanation of symbols]

[0109] 1. Exterior materials for power storage devices 2...Heat-resistant resin layer (outer layer) 3…Thermofusible resin layer (inner layer) 4…Metal foil layer 7…Protective resin layer 8...Spacer agent (spacer agent aggregate) H…protruding height (protruding height of part of the spacer agent from the surface of the protective resin layer) W: Major axis of spacer aggregate in plan view

Claims

1. An exterior material for an electricity storage device, comprising a heat-resistant resin layer as an outer layer, a heat-fusible resin layer as an inner layer, and a metal foil layer disposed between the two layers, A protective resin layer is laminated on the outer side of the heat-resistant resin layer, the protective resin layer contains a resin and a spacer agent that is incompatible with the resin, a part of the spacer agent protrudes outward from a surface of the protective resin layer; The spacer agent has an average particle size of 1 μm to 20 μm; the thickness of the protective resin layer (thickness after drying; excluding the protruding portion of the spacer agent) is 0.5 μm to 10 μm, The exterior material for an electricity storage device, wherein the spacer agent has a weight average molecular weight in the range of 1,000 to 8,000.

2. The density of the spacer agent is 0.85 g / cm 3 ~3.0g / cm 3 The electrical storage device packaging material according to claim 1 ,

3. 3. The packaging material for an electricity storage device according to claim 1, wherein the spacer agent is contained in the protective resin layer in the form of an aggregate of a plurality of spacer agent particles.

4. 4. The exterior material for an electricity storage device according to claim 3, wherein the average major axis of the spacer agent aggregates in the protective resin layer in a plan view is in the range of 10 μm to 120 μm.

5. 5 . The exterior packaging material for an electricity storage device according to claim 3 , wherein the spacer agent aggregates protrude outward from the surface of the protective resin layer to a height of 1 μm or more.

6. The exterior material for a storage battery device according to any one of claims 3 to 5, wherein the planar area of ​​a protruding portion having a protruding height of 1 μm or more protruding outward from the surface of the protective resin layer is 4% to 20% of the entire planar area of ​​the protective resin layer.

7. The exterior material for an electricity storage device according to any one of claims 1 to 6, wherein the spacer agent is one or more types of spacer agents selected from the group consisting of waxes and polymer powders.

8. The exterior packaging material for an electricity storage device according to any one of claims 1 to 7, wherein the spacer agent has a melting point of 90°C to 350°C.

9. The exterior material for an electricity storage device according to any one of claims 1 to 8, wherein a content of the spacer agent in the protective resin layer is 2% by mass to 20% by mass.

10. The packaging material for an electricity storage device according to any one of claims 1 to 9, wherein the resin is a reaction product resin of a polyol and a polyisocyanate.

11. The protective resin layer further contains a matting agent composed of fine particles, and when viewed in plan, the average major axis of the matting agent in the protective resin layer is in the range of 0.3 μm to 7 μm.

12. An exterior case for an electricity storage device, comprising a molded article of the exterior material for an electricity storage device according to any one of claims 1 to 11.

13. A main body of the electricity storage device; An exterior member comprising the exterior material for an electricity storage device according to any one of claims 1 to 11 and / or the exterior case for an electricity storage device according to claim 12, The power storage device, wherein the power storage device main body is exteriorly covered with the exterior member.

Citation Information

Patent Citations

  • Laminated material for secondary battery container and secondary battery container

    JP2003288865A

  • Packaging material for electrochemical cell

    JP2011054563A

  • Laminate for battery case and secondary battery

    JP2012009314A

  • Laminate for battery outer packaging and secondary battery

    JP2013118083A

  • Wrapping material for battery case

    JP2014044806A